Three critical hydrogen bonds determine the catalytic activity of the Diels-Alderase ribozyme - Kraut, Stefanie; Bebenroth, Dirk; Nierth, Alexander; Jäschke, Andres (Nucleic acids research, 2012)
Abstract. Compared to protein enzymes, our knowledge about how RNA accelerates chemical reactions is rather limited. The crystal structures of a ribozyme that catalyzes Diels–Alder reactions suggest a rich tertiary architecture responsible for catalysis. In this study, we systematically probe the relevance of crystallographically observed ground-state interactions for catalytic function using atomic mutagenesis in combination with various analytical techniques.
Published online 5 October 2011
Gesehen am 19.11.2018